Susceptibility to tobacco use and associated factors among youth in five central and eastern European countries - Kinga Polanska; Malgorzata Znyk; Dorota Kaleta (BMC, 2022)
Abstract Background Tobacco use among young people still remains a major public health problem. Thus, the aim of this study was to perform a cross-country comparison for the factors associated with susceptibility to tobacco use among youth from five central and eastern European countries. Methods The data used in the current analysis, focusing on youth (aged 11-17 years), who have never tried or experimented with cigarette smoking, was available from the recent Global Youth Tobacco Survey (Czech Republic (2016), n = 1997; Slovakia (2016), n = 1998; Slovenia (2017), n = 1765; Romania (2017), n = 3718; Lithuania (2018), n = 1305). Simple, multiple logistic regression analyses and random-effect meta-analysis were conducted to identify factors associated with tobacco use susceptibility as the lack of a firm commitment not to smoke. Results Nearly a quarter of the students were susceptible to tobacco use in 4 of 5 countries. The following factors were identified, consistently across countries, as correlates of tobacco use susceptibility: exposure to passive smoking in public places (AOR from 1.3; p = 0.05 in Slovakia to 1.6; p < 0.01 in Czech Republic and Romania), peers smoking status (AOR from 1.8 p < 0.01 in Slovakia to 2.5; p < 0.01 Lithuania), opinion that smoking helped people feel more comfortable at celebrations (AOR from 1.3; p = 0.01 in Czech Republic to 1.9; p < 0.01 in Lithuania), noticing people using tobacco in mass media (AOR 1.5; p < 0.01 in Slovenia and 1.6; p < 0.01 in Lithuania), lack of knowledge on harmful effects of passive smoking (AOR 1.8; p < 0.01 in Slovakia and 2.4; p < 0.01 in Slovenia), lack of antismoking education provided by school (AOR 1.3; p < 0.05 in Czech Republic, Slovakia and Slovenia; 1.9; p < 0.01 in Lithuania), and family (AOR 1.5; p < 0.01 in Slovenia and Romania). Moreover those who believed that smoking makes young people look less attractive (AOR from 0.5; p < 0.01 in Romania to 0.7; p = 0.05 in Lithuania) and that people who smoke have less friends (AOR 0.7; p ≤ 0.06) turned out to be less susceptible to tobacco use initiation. In Czech Republic and Slovenia significantly higher susceptibility to tobacco use was observed among females as compared to males (AOR 1.4; p < 0.01), whereas in Romania opposite pattern, although not significant, was observed (p = 0.3). Having more money available for own expenses, positively correlated with smoking suitability in all countries (AOR > 1.5; p < 0.01) except Lithuania where youth with more money available tend to be less susceptible to tobacco use (p > 0.05). Youth who share the opinion that people who smoke have more friends were more susceptible to smoking in Romania (AOR 1.4; p = 0.04) but tend to be less susceptible in other countries. Exposure to advertisements at points of sale was significant correlate of tobacco use susceptibility in Slovakia and Slovenia (AOR 1.4 and 1.5 respectively; p < 0.05), with moderate heterogeneity between the countries. Conclusions A high proportion of youth from central and eastern European countries was susceptible to tobacco use. Social factors, and those related to educational and policy issues as well as to attitudes regarding tobacco use were strongly, and consistently across countries, correlated with tobacco use susceptibility. Slight differences in susceptibility to tobacco use between the countries were related to: sex, money available for own expenses, exposure to advertisements at points of sale and opinion that people who smoke have more friends. These factors should be considered when designing and implementing anti-tobacco activities among young people.